PENGARUH LOKASI USAHA, KUALITAS PELAYANAN DAN KUALITAS JASA TERHADAP KEPUASAN KONSUMEN PADA USAHA JASA LAUNDRY DI WILAYAH PEJENG (Widyadari : Jurnal Pendidikan, 2021)
This study aims to analyze the effect of business location, service quality, and service quality on customer satisfaction in the laundry service business in the Pejeng area. The results showed that (1) the business location variable (X1) had a significant effect on Customer Satisfaction (Y) in the laundry service business in the Pejeng area, (2) the service quality variable (X2) had a significant effect on Customer Satisfaction (Y). Laundry service business in pejeng area, (3) Service quality variable (X3) has a significant influence on Customer Satisfaction (Y) on laundry service business in Pejeng area, (4) Variable business location, service quality and service quality have a simultaneous effect on satisfaction consumers in the laundry service business in the pejeng area, with the results of the F-table (Ft 5%), namely 3.09 where the F-count is greater than F-table (83.090> 3.09) with a significant value of 0.000 <0.005. The coefficient of determination using the Adjusted R Square method is 0.722, which means that 72.2% of business location (X1), Service Quality (X2) and Service Quality (X3) affect consumer satisfaction in laundry service businesses in the pejeng area, while the remaining 27, 8% is influenced by other factors that are not included in the research variables.